EDITORIAL EXPERIENCE AT JOURNAL OF AYUB MEDICAL COLLEGE ABBOTTABAD (JAMC) - Ayub, Muhammad (Journal of Ayub Medical College Abbottabad, 2013)
Editorship of a scientific journal is a very tough task and demands whole-time efforts to maintain the academic and technical standards of the journal. As publication of research work in standard medical journals is mandatory for appearing in the postgraduate examination, selection for a job, and subsequent promotion, the editors receive a lot of scientific work for possible publication, and they face a lot of pressure for an early publication. The authors demand facilitation for quick publication of their work, and the editors have to look into the standard of the output. Keeping a balance between demands and supply is very hard and some times culminates into rejection of or delay in publication of an article, mostly resulting in a complaint from the authors. The editors must not compromise on the standard of their output under any circumstances.